Role of TP53 Mutations in Surgical Decision-Making and Prognosis of Head and Neck Cancers - Zaidi , Syeda Umm E Abeeha; Iqbal , Naveed; Adeel-Ur-Rehman; Rauf, Manal; Tariq, Roha; Khalid Jamil, Javeria Binte (Indus Journal of Bioscience Research, 2025)
Researchers studied changes in the TP53 gene for 200 people with head and neck squamous cell carcinoma (HNSCC), who were receiving care at advanced hospitals. TP53 gets this name because it helps manage cell growth, repair broken DNA and gets rid of defective cells. When something happens to this gene, it can support tumor growth and make it harder for treatments to work. Researchers noted that TP53 gene mutations were present in about 60% of the patients, with most of these mutations being missense, meaning they might stop the gene from functioning or switch its role so it can support cancer growth. According to a Chi-square test, patients with TP53 mutations often had different surgery and adjuvant therapy compared to patients without the mutation. For those with congenital heart disease and genes changed, surgeons usually had to perform extra surgeries and consider using chemotherapy or radiation. It was also found from logistic regression that tumors with TP53 mutations have a higher chance of returning and are often more likely to end in the patient’s death. Those with the mutations had over three times higher risk of tumors recurring and nearly three times higher risk of passing away than those without the mutations. Based on these results, testing TP53 in patients could help doctors choose better treatments and shows that newer therapies are required for those with these gene changes.